DEGRADATION OF CONVENTIONAL AND OXYBIODEGRADABLE PLASTIC BAGS SUBMETTEED TO ACID AND BASIC GIDROLYSIS PROCESSES - de Souza, W. M.; Coelho, L. R. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The increased use of plastic bags has created a major problem in their disposal, which is often done in inappropriate places. As an alternative to this problem, the chemical recycling of polymeric materials via depolymerization by hydrolysis, which consists in the reaction of the polymer with excess water in the presence of a catalyst and heating, resulting in the recovery of the starting monomers, has been widely discussed. The present study aimed to analyze the degradation of conventional and post-consumer oxy-biodegradable plastic bags through the hydrolysis reaction in acidic and basic medium. The experiment was composed by a 2 x 4 factorial scheme, where respectively corresponds to the bag type versus different reagents, and 4 x 3, where respectively corresponds to different reagents versus different concentrations, totaling 24 samples. In the first week the solutions containing the samples were conditioned at room temperature, while in the second week they were stored in a greenhouse and kept at 70ºC, after this period the samples were removed from the greenhouse and washed with distilled water, to be made. drying of reagents. The best result was observed in test N13, where the percentage of mass loss was 27.08%. The worst result was in sample B18, which obtained a mass gain of 110.14%. With this work it is concluded that the degradation was significant only in conventional bags and that it is possible to use this technique in the creation of technological alternatives that combat the growing neglect with the environment.